Performance optimisation of a solar air heater for heating and ventilating : a comparative study contributing to New Zealand classrooms : a thesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy (Ph.D.) in Built Environment at Massey University, Auckland, New Zealand - Pardeshi, Poonam (Massey University, 2025)
New Zealand primary schools often fail to meet the World Health Organization (WHO) and American Society of Heating, Refrigerating, and Air-Conditioning Engineers (ASHRAE) standards for winter ventilation and temperature. Poor indoor air quality affects health, well-being, and learning, highlighting the need for better ventilation. Furthermore, strict energy caps in schools make affordable heating and ventilation solutions essential. Since school hours largely coincide with peak solar radiation, solar energy presents a cost-effective pathway to address these challenges. Solar air heaters (SAHs) have the potential to provide space heating and ventilation simultaneously. However, their application is limited by low thermal efficiency, primarily due to internal and external heat losses. The central research question of this study is: how can the performance of SAHs be optimised to provide effective, low-cost heating and ventilation for New Zealand classrooms? To address this question, three optimisation strategies were explored at Massey University in 2023. The first examined operational adjustments to a finned-tube SAH with corrugated fins (FT-SAH) under different fan speeds and seasons. The second experiment tested the finned tube SAH with fin inserts (treatment) and without fin inserts (control) to investigate the effect of fin inserts on its thermal performance. The third investigated material optimisation using nanocoated absorber tubes. These approaches collectively aimed to identify pathways for improving SAH performance for classroom heating and ventilation. The first experiment tested a novel FT-SAH under New Zealand climatic conditions: Case Study 1 at 100% fan speed in winter, and Case Study 2 at 50% fan speed in spring. Results showed a trade-off between airflow, temperature gain, and thermal efficiency. At higher fan speeds (Case Study 1), the system achieved higher mass flow rates, with daily averages ranging from 0.054 to 0.059 kg/s (mean: 0.056 kg/s), and ventilation capacity ranging from 164.2 to 175.3 m³/h (mean: 172.4 m³/h). However, this resulted in only moderate outlet temperatures (17.3–49.3 °C, mean: 29.4 °C), lower temperature rise (ΔT) values (6.0–32.6 °C, mean: 15.9 °C), and decreased thermal efficiency (38.6–83.8%, mean: 69.6%). In contrast, under lower fan speeds (Case Study 2), the FT-SAH produced higher outlet temperatures (24.4–59.0 °C, mean: 39.9 °C) and greater ΔT values (10.2–41.3 °C, mean: 24.1 °C). However, this was accompanied by reduced airflow (0.022–0.025 kg/s, mean: 0.024 kg/s), lower ventilation (69.9–77.0 m³/h, mean: 74.8 m³/h), and decreased thermal efficiency (23.8–34.7%, mean: 29.4%). These findings highlight that high fan speeds favour ventilation, while low fan speeds enhance heating. However, in both cases, the FT-SAH alone did not meet the minimum ventilation rates recommended by the New Zealand Ministry of Education (MOE). Future work should focus on optimising FT-SAH operation to balance ventilation and heating, particularly by increasing the volume of warm air supplied while maintaining outlet air temperatures near 18.0 °C to support classroom comfort. In the second experiment, the FT-SAH was tested under two configurations: tubes with corrugated fins (treatment) and tubes without fins (control). At high fan speed (ṁ = 0.07 kg/s), the treatment achieved higher outlet temperatures of 25.4 °C compared to 22.3 °C for the control, along with a larger temperature rise of 7.0 °C compared to 4.4 °C, and a greater efficiency of 72.6% compared to 44.5%. At a low fan speed (ṁ = 0.04 kg/s), the treatment again outperformed the control, reaching outlet temperatures of 29.4 °C, a temperature rise of 10.4 °C, and an efficiency of 57.0%, compared to 25.3 °C, 6.3 °C, and 33.4%, respectively. These results demonstrate that the addition of corrugated fins substantially enhanced heat transfer and overall thermal efficiency under both operating conditions, confirming the effectiveness of the modified finned-tube design for classroom heating and ventilation applications. The third experiment investigated nanocoated absorber tubes using aluminium oxide (Al₂O₃) and copper oxide (CuO) in black paint. A 4% Al₂O₃/black paint coating with fin inserts improved thermal efficiency by 37.5% compared to the control and increased outlet air temperatures by up to 16.4 °C. Although these tubes were tested without a cover, insulation, or frame, the results demonstrated the potential of nanocoating to improve performance further. Tubes integrated into a box (SAH) must be investigated for thermal performance. Overall, the study shows that while a single FT-SAH unit cannot independently achieve the required classroom ventilation rates, performance optimization through fin design and nanocoating can substantially improve thermal output. For practical classroom application, multiple SAH units, integrated with insulation and proper casing, would be required to meet both heating and ventilation demands
The following Figures were removed for copyright reasons: 2-4 (=Fan et al., 2019 Figs 2 & 1 respectively), 2-6 (=Afshari et al., 2020 Fig 2), 2-7 (=Sözen et al., 2020 Fig 7), 2-8 (=Souayeh et al., 2021 Fig 1(c) i-iii). Figure 2-5 is reproduced under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International license.
Keywords: 330206 Building science, technologies and systems